2020
DOI: 10.1126/science.aaz3090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regeneration-responsive enhancers shape regenerative capacities in vertebrates

Abstract: Vertebrates vary in their ability to regenerate, and the genetic mechanisms underlying such disparity remain elusive. Comparative epigenomic profiling and single-cell sequencing of two related teleost fish uncovered species-specific and evolutionarily conserved genomic responses to regeneration. The conserved response revealed several regeneration-responsive enhancers (RREs), including an element upstream to inhibin beta A (inhba), a known effector of vertebrate regeneration. This element activated expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
166
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(172 citation statements)
references
References 65 publications
4
166
1
1
Order By: Relevance
“…Additionally, changes in regeneration-responsive enhancers of mammals might be another reason for less regenerative capacities in mammals, when compared to zebrafish. This was recently suggested for the inhibin beta A gene [ 177 ]. Furthermore, they display an immune response allowing an enhanced regeneration [ 96 , 178 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, changes in regeneration-responsive enhancers of mammals might be another reason for less regenerative capacities in mammals, when compared to zebrafish. This was recently suggested for the inhibin beta A gene [ 177 ]. Furthermore, they display an immune response allowing an enhanced regeneration [ 96 , 178 ].…”
Section: Discussionmentioning
confidence: 88%
“…Last, but not least, a comprehensive understanding of the mechanisms by which the glial scar is transiently generated and resolved in zebrafish could open a way for promoting brain regeneration in mammals and avoiding the consequences of brain damage. In addition, it could also be argued that mammals lost the ability to drive the expression of key genes involved in the regenerative process, due to a major regulatory change in their expression following injury [ 177 ]. Interestingly, studies on invertebrates such as drosophila also demonstrate common strategies in neurogenesis and brain repair with mammals and highlight the role of blood vessels in these mechanisms [ 185 , 186 ].…”
Section: Discussionmentioning
confidence: 99%
“…We show that treatment-persistent cells have high cell cycle turnover, compatible with high regenerative potential (Poli et al, 2018; Wang et al, 2020), and assume states of stemness from their transcriptional profiles. As these features have been associated with more aggressive tumors, we developed transcriptional signatures derived from two states in particular: one state derived in ADT-treated mice prostate cells by Karthaus et al (Karthaus et al, 2020), which we renamed PROSGenesis and which tightly associated with initial and enzalutamide-induced clusters in our model of enzalutamide resistance, and one that we called “Stem-Like”, associated with persistent cells during evolution of enzalutamide resistance.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to TFs, enhancers also have great significance in regeneration. The conserved teleost regeneration response enhancers in zebrafish and African killifish (Nothobranchius furzeri) were uncovered by histone H3K27ac chromatin immunoprecipitation sequencing (ChIPseq, a marker for active enhancers), bulk RNA sequencing (RNA-seq), and single-cell RNA sequencing (scRNA-seq) (Wang et al, 2020). These studies suggested that epigenetic regulatory elements play fundamental roles in regeneration.…”
Section: Introductionmentioning
confidence: 99%